Development and Evaluation of Glycine max Germplasm Lines with Quantitative Resistance to Sclerotinia sclerotiorum - McCaghey, Megan; Willbur, Jaime; Ranjan, Ashish; Grau, Craig R.; Chapman, Scott; Diers, Brian; Groves, Carol; Kabbage, Mehdi; Smith, Damon L. (Frontiers in Plant Science, 2017)
Sclerotinia sclerotiorum, the causal agent of Sclerotinia stem rot (SSR), is a devastating fungal pathogen of soybean that can cause significant yield losses to growers when environmental conditions are favorable for the disease. The development of resistant varieties has proven difficult. However, poor resistance in commercial cultivars can be improved through additional breeding efforts and understanding the genetic basis of resistance. The objective of this project was to develop soybean germplasm lines that have a high level of SSR resistance to be used directly as cultivars or in breeding programs as a source of improved SSR resistance. SSR-resistant soybean germplasm was developed by crossing two sources of resistance, W04-1002 and AxN-1-55, with lines exhibiting resistance to other pathogens such as Heterodera glycines and Cadophora gregata. Following greenhouse evaluations of 1,076 inbred lines derived from these crosses, 31 lines were evaluated for resistance in field tests during the 2014 field season. Subsequently, 11 SSR resistant breeding lines were moved forward for field evaluation in 2015, and seven elite breeding lines were selected and evaluated in the 2016 field season. To better understand resistance mechanisms, a marker analysis was conducted to identify quantitative trait loci (QTL) linked to resistance. Thirteen markers associated with SSR resistance were identified on chromosomes 15, 16, 17, 18, and 19. Our markers confirm previously reported hot spots associated with SSR resistance, as well as novel genetic regions of interest. The 7 elite germplasm lines were also re-evaluated within a greenhouse setting using a cut petiole technique with multiple S. sclerotiorum isolates to test the durability and confirm physiological resistance of these lines in a controlled environment. In these studies, we identify 4 germplasm lines; 91-38, 51-23, SSR51-70, and 52-82B exhibiting a high level of SSR resistance combined with desirable agronomic traits, including high protein and oil contents. While many of the experimental lines have excellent physiological resistance, yield and agronomic performance of these lines need to be further improved before they can be used as elite commercial cultivars. However, the germplasm stock identified in this study will serve as a valuable source of physiological resistance to SSR